CLASS AND GENDER INJUSTICE IN OKKY MADASARI’S ENTROK: A MARXIST-FEMINIST ANALYSIS - Saragih, Revi Br; Zuhriah, Lailatul; Ramadhani, Shofi; wati, Rahma (Universitas Muhammadiyah Lampung, 2025)
This study aims to analyze class and gender injustice in the Entrok work by Okky Madasari through the theory approach of Marxist Feminism. The background of this study is based on the limitations of previous studies that have not been fully integrated the relationship between economic oppression and gender subordination in the sociopolitical context of the New Order. This study uses a descriptive qualitative method with the main source in the form of an entry novel text, and the focus of analysis is directed at narrative structures, character development, and important dialogues that reflect social inequality. The theory of Marxist feminism, especially Heidi Hartmann's ideas, was used to understand how capitalism and patriarchy work simultaneously in oppressing lower class women. The findings show that women in the novel experience layered oppression: economically as part of the exploited working class, and socially as victims of patriarchal norms that limit their roles and rights. Symbols such as entrepreneurs become a representation of women's desires for freedom and self-recognition. Critical awareness of Sumarni figures over the division of gender-based labor reflects the potential resistance to oppressive structures. The results of this research are nine data, including four data of class injustice and five data of gender injustice. In conclusion, novel entrok not only illustrates the social reality of oppressed women, but also offers alternative narratives that ignite class and gender awareness. This study contributes to the development of a more intensurctional and relevant feminist literary study to the issue of today's social justice.